The Effect of Dividend and Divisor Learning Media on Fifth-Grade Students’ Understanding of Division Concepts - Muarif, Agus Fajar; Nasution, Ismail Saleh (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study aims to determine the effect of the use of DND (Dividend and Divisor) learning media on the understanding of division material in fifth-grade students of Sanggar Belajar Kampung Baru Malaysia. Mathematics learning, especially on division material, is often considered difficult by students because it is abstract and requires a strong understanding of concepts. Therefore, learning media are needed that can help students understand the concept of division in a concrete and interesting way. This study uses a quantitative approach with an experimental research type and a one-group pretest-posttest design. The research subjects consisted of 11 fifth-grade students. Data collection techniques were carried out through tests and documentation. The research instrument was in the form of multiple-choice questions that had been tested for validity and reliability. The data obtained were analyzed using the Paired Sample t-Test. The results of the study showed a significant increase in student understanding after the use of DND learning media. The average pretest score of 45.45 increased to 81.82 in the posttest. The results of the Paired Sample t-Test showed a significance value of 0.000 (p < 0.05), which means there was a significant difference between learning outcomes before and after the use of DND media. These findings indicate that the Dividend and Divisor learning media is effective in improving students' understanding of the concept of division. Therefore, DND media can be used as an innovative and effective alternative learning medium in elementary school mathematics, particularly for division.